UMPSA validates three regulatory Programmes at Muscat College, Oman - Zahiruddin, Mohd Zain (UMPSA, 2024)
MUSCAT, OMAN, 5 November 2024 – A delegation from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), led by the Dean of the Faculty of Computing (FK), Associate Professor Ts. Dr. Adzhar Kamaludin, and the Dean of the Faculty of Industrial Management (FPI), Dr. Mohd Hanafiah Ahmad, visited Muscat College in Oman to validate three regulatory programmes offered by the college in collaboration with UMPSA.